Applications of hurdles in the processing of snail (Achachatina marginata) meat - Eke, Mike O; Kukwa , R E (Journal of Postharvest Technology, 2022)
Inadequate protein consumption is one of the major challenges in most developing countries especially in Africa both to urban and rural dwellers. Snail meat was processed into dried snails using salt, sugar and citric acid at different concentrations of 0.1% (B), 0.2% (C), 0.3% (D), and 0.5% (E). The control sample (Sample A) was without treatment. Analyses of minerals, vitamins, proximate and anti-nutritional properties were carried out using standard methods. All results showed statistical difference (P<0.05%). The minerals sodium, iron, potassium, calcium, phosphorus, zinc and magnesium ranged from 71.350 to 99.420 mg/100g, 12.335 to 15.715 mg/100 g, 853.235 to 901.040 mg/100 g, 86.560 to 97.570 mg/100 g, 498.560 to 701.215 mg/100 g, and 52.450 to 76.250 mg/100 g and163.230 to 128.00 mg/100 g respectively. The vitamin A, B1, B2, B3, B6 and E ranged from 6.595 to 9.685 µg/100 g, 0.160 to 0.280 mg/100 g, 0.330 to 0.390 mg/100 g, 0.165 to 0.300 mg/100 g, 0.054 to 0.073 mg/100 g and 0.955 to 0.715 mg/100 g respectively. The proximate composition of snail meat: the crude protein, crude fat, ash, moisture and carbohydrate content of the samples ranged from 56.450 to 63.515%, 1.550 to 2.110%, 7.610 to 8.850%, 9.000 to 7.200% and 25.280 to 18.325% respectively. Crude fibre was not detected in the samples. The pH value of the snail meat ranged from 6.25 to 4.60. Anti-nutrients such as oxalate, tannin and cyanide were detected, oxalate ranged from 0.00-0.01%, tannin 0.00 - 0.01% and cyanide 0.00 – 0.01%. Phytate was not detected. This study shows that snails’ meat can be treated with salt, sugar and citric acid and the samples treated with 0.3 and 0.5% are considered to be richer in nutrients.